2013
DOI: 10.1007/s12032-013-0770-x
|View full text |Cite
|
Sign up to set email alerts
|

Intact expression status of RASSF1A in acute myeloid leukemia

Abstract: As a typical tumor suppressor gene, transcriptional silencing of ras-association domain family 1, isoform A (RASSF1A) is caused by biallelic methylation or the condition that one allele is methylated and then the other allele lost by allelic loss, as second hit. RASSF1A is inactivated epigenetically and thus down-regulated in many solid tumors. In summary, for the first time, we analyzed the expression status of RASSF1A in a cohort of 56 de novo acute myeloid leukemia (AML) patients using quantitative real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In lung cancer, it was found that there are eight CpGs in the promoter area and six in the first exon that transcriptionally are more important than the other CpGs [ 46 ]. In breast cancer, it also has been shown that RASSF1A methylation has a progressive nature starting in the first exon and spreading into the promoter and promoter methylation (not exon 1 methylation) correlated with RASSF1A expression silencing [ 47 ]. However, the extent of methylation at individual CpG sites remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, it was found that there are eight CpGs in the promoter area and six in the first exon that transcriptionally are more important than the other CpGs [ 46 ]. In breast cancer, it also has been shown that RASSF1A methylation has a progressive nature starting in the first exon and spreading into the promoter and promoter methylation (not exon 1 methylation) correlated with RASSF1A expression silencing [ 47 ]. However, the extent of methylation at individual CpG sites remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients’ ( n = 128) in the range of 16–60 years, for whom diagnostic peripheral blood (PB) ( n = 76 with blast ≥30%) or bone marrow (BM) ( n = 52), samples were available and were included after obtaining Institutional Review Board approval and informing consent in accordance with the Declaration of Helsinki. Because of common treatment and to have a larger sample size, samples from previous studies were included . The patients were classified according to the French–American–British (FAB) Cooperative Group Criteria .…”
Section: Methodsmentioning
confidence: 99%
“…NM_005157.5) as recommended by Europe Against Cancer Program as reference gene (primer pairs are listed in Table ). Construction of standard curves for quantitation of BECN1 variants and the internal control ABL1 , and calculation of BECN1 normalized to ABL1 was performed as previously reported . As our analysis showed that the expression of BECN1 does not differ between our samples from PB or BM ( P = 0.109), we determined BECN1 expression levels in leukocytes form PB samples of 30 healthy age‐matched volunteers as control [median = 2.87, mean = 4.45 (95% CI: 2.61–6.29, standard deviation = 4.92, standard error of mean = 0.90)].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, in acute myeloid leukemia, RASSF1A methylation occurs very rarely if ever (please see Table 1 in [127]) and RASSF1A expression is not affected [128] suggesting that RASSF1A is not involved in the pathogenesis. It will be interesting to determine why RASSF1A, which is methylated in such an extent in other tumors, remains intact in myeloid malignancy.…”
Section: Epigenetic Regulation Of the Rassfsmentioning
confidence: 99%